Validation of APACHE IV score in postoperative liver transplantation in southern Brazil: a cohort study - Rodrigues Filho,Edison Moraes (2019)
Abstract Background: Liver transplantation is the only curative therapeutic modality available for individuals at end-stage liver disease. There is no reliable method of predicting the early postoperative outcome of these patients. The Acute Physiology and Chronic Health Evaluation (APACHE) is a widely used model for predicting hospital survival and benchmarking in critically ill patients. This study evaluated the calibration and discrimination of APACHE IV in the postoperative period of elective liver transplantation in the southern Brazil. Methods: This was a clinical prospective and unicentric cohort study that included 371 adult patients in the immediate postoperative period of elective liver transplantation from January 1, 2012 to December 31, 2016. Results: In this study, liver transplant patients who evolved to hospital death had a significantly higher APACHE IV score (82.7 ± 5.1 vs. 51.0 ± 15.8; p < 0.001) and higher predicted mortality (6.5% [4.4-20.2%] vs. 2.3% [1.4-3.5%]; p < 0.001). The APACHE IV score showed an adequate calibration (Hosmer-Lemeshow - H-L = 11.37; p = 0.181) and good discrimination (Receiver Operator Curve - ROC of 0.797; Confidence Interval 95% - 95% CI 0.713-0.881; p < 0.0001), although Standardized Mortality Ratio (SMR = 2.63), (95% CI 1.66-4.27; p < 0.001) underestimate mortality. Conclusions: In summary, the APACHE IV score showed an acceptable performance for predicting a hospital outcome in the postoperative period of elective liver transplant recipients.